Potensi Bahan Alami dalam Menekan Produksi CH4 dan N2O dari Tanah Sawah - Helena Lina Susilawati; Anicetus Wihardjaka; Nurhasan Nurhasan; Prihasto Setyanto (Jurnal Ilmu Pertanian Indonesia, 2021)
Low nitrogen efficiency is one of the sources of greenhouse gas (GHG) emissions from rice fields. Methane (CH4) and nitrous oxide (N2O) emissions could be controlled by nitrification inhibitors (NI). However, NI that has been commercialized is expensive. Therefore, some natural materials should be developed as NI that is low cost, easy to use, low N2O and CH4, and eco-friendly. The objective of this study was to observe the effect of natural NI on the production potential of CH4 and N2O from paddy soil. The experiment in the laboratory was arranged in a factorial design (2 × 7 × 3 replication). The first factor was soil types (inceptisols and vertisols), and the second factor was natural NI (control, Cocos nucifera, Camellia sinensis, Coffea robusta, Curcuma domestica, Ageratum conyzoides). The results showed that the average CH4 production from the natural NI in the inceptisols and vertisols ranged 0,014-1,710 mg CH4 g soil-1 and 0,002-0,337 mg CH4 g soil-1, respectively. Application of natural NI reduced 32-69% CH4 production compare to control. Redox potential affected CH4 production. The chemical compound of the natural NI affected CH4 production in the soil. The application of coffee waste, coconut husk, tea waste, and Ageratum conyzoides reduced 60,71; 54,61; 64,83 dan 64,16% of N2O production in Inceptisols compare to control, respectively. Application of natural NI could contribute to save the environment because it decreased GHG production in paddy soil. Keywords: greenhouse gas, inceptisols, incubation experiment, natural nitrification inhibitors, vertisols